(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
Over-potential or high Potential tests are frequently applied to machine stator windings to assure that the electrical insulation in windings is fit for service. However, several questions are frequently raised: When should a high Potential test be applied? Which high Potential test should be applied? What should be the high Potential test levels? Does high Potential test damage a good high potential winding? To answer these questions, a comprehensive review of literature was done and industry experts were surveyed for their views and experience under an EPRI sponsored project. The results are summarized in this paper. The questions are answered using the information from the literature review and the survey responses.